Proceedings of the 7th ACM International Conference on Bioinformatics, Computational Biology, and Health Informatics 2016
DOI: 10.1145/2975167.2985672
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy design for maximizing sensitivity and minimizing toxicity

Abstract: Background: Design of personalized targeted therapies involve modeling of patient sensitivity to various drugs and drug combinations. Majority of studies evaluate the sensitivity of tumor cells to targeted drugs without modeling the effect of the drugs on normal cells. In this article, we consider the individual modeling of drug responses to tumor and normal cells and utilize them to design targeted combination therapies that maximize sensitivity over tumor cells and minimize toxicity over normal cells. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Each set contains cell lines from two separate cancer types. The cell lines are modeled on a proliferation network structure based on target inhibition maps 28 , 29 . We have chosen to model each cell line utilizing a single block where each block contains a set of kinases, ϕ , connected in parallel.…”
Section: Resultsmentioning
confidence: 99%
“…Each set contains cell lines from two separate cancer types. The cell lines are modeled on a proliferation network structure based on target inhibition maps 28 , 29 . We have chosen to model each cell line utilizing a single block where each block contains a set of kinases, ϕ , connected in parallel.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, combination treatment with low concentration of SCH 529074 and the autophagy inhibitor CQ led to reduced tumor cell survival rates compared with those observed following single drug treatment, indicating the efficacy of this combination therapy in NSCLC cells. It has been previously revealed that the application of combination therapy can maximize sensitivity and minimize the toxicity observed in the treatment of cancer cells (38). The precise role of SCH 529074 in autophagy requires further investigation by the analysis of additional autophagic markers.…”
Section: Discussionmentioning
confidence: 99%
“…Probabilistic Target Inhibition Map (PTIM) modeling [13][14][15][16][17][18] integrates patient-specific chemical screening data with matched genomic and transcriptomic sequencing data to design personalized drug combinations. PTIM modeling identifies drug combinations where the individual agents may not slow or stop tumor growth but in combination will be synergistic and slow tumor growth.…”
Section: Probabilistic Target Inhibition Map Modelingmentioning
confidence: 99%